Writing Industrial Change in Urdu: Artisanship, Islam and Technology in Colonial India. Issue 4 (4th July 2021) - Lanzillo, Amanda M.
Abstract: Artisans in late nineteenth and early twentieth century India engaged with industrial change through vernacular-language manuals that explained new technologies and practices using regional cultural, literary and religious references. This article analyses the development, circulation and use of manuals written in Urdu for trades including metal smithing, masonry and carpentry. Urdu-language artisan manuals drew on both European-authored industrial textbooks and earlier Persian-language styles of writing about craftsmanship. The article argues that these late nineteenth and early twentieth century manuals shaped artisan training by rooting new technologies in regional literary and religious traditions and by articulating a perceived Islamic past for artisan trades.